Systemic effects of the vapor pressure deficit on the physiology and productivity of protected vegetables - Xuemei Yu; Yuhui Zhang; Xiaofan Zhao; Jianming Li (Vegetable Research)
In previous decades, the global temperature has risen, and the saturation vapor pressure deficit (VPD) has increased. VPD is an important environmental factor affecting crops, especially their yields. However, the effects of various VPD conditions on water transport dynamics, anatomical structure, stomatal morphology, photosynthetic physiology, nutrient absorption, yield, and quality remain unclear. Many studies have shown that atmospheric transpiration is enhanced, water transport dynamics in the soil-plant-atmosphere continuum and water potential gradient are increased, and crop water potential is reduced under high VPD. Crops have undergone a series of changes that have enhanced their adaptation to high-VPD environments. Mesophyll thickness and conductance and stomatal size and conductance have decreased, and this has led to reductions in the photosynthetic rate and nutrient accumulation. High VPD seriously reduces the yield and water use efficiency of protected vegetables but improves fruit color and flavor quality. Reductions in VPD can improve water and nutrient transport in protected vegetables, alter the anatomical structure of crops, promote crop photosynthesis, and increase fruit yield, nutritional quality, and water use efficiency. Comprehensive analysis of the effect of VPD on the physiology and productivity of protected vegetables will provide insights that will aid the cultivation of protected vegetables with high quality and yield.